The role of the Technical Review Panel of the Global Fund to Fight HIV/AIDS, Tuberculosis and Malaria: an analysis of grant recommendations. Issue 3 (4th January 2018) - Schmidt-Traub, Guido
Abstract: The independent Technical Review Panel (TRP) of the Global Fund to Fight HIV/AIDS, Tuberculosis and Malaria is a unique mechanism to review funding proposals and to provide recommendations on their funding. Its functioning and performance have received little attention in the scientific literature. We aimed to identify predictors for TRP recommendations, whether these were in line with the Global Fund's ambition to give priority to countries most in need, and whether they correlated with grant performance. We combined data on proposals and applications under the Rolling Continuation Channel, TRP recommendations and grant implementation during the rounds-based mechanism (2002–2010) with country characteristics. Ordered logistic and OLS regressions were used to identify predictors for per-capita funding requests, TRP recommendations, Global Fund funding and grant performance ratings. We tested for financial suppression of large funding proposals and whether fragile or English-speaking countries performed differently from other countries. We found that funding requests and TRP recommendations were consistent with disease burden, but independent of other country characteristics. Countries with larger populations requested less funding per capita, but there is no evidence of financial suppression by the TRP. Proposals from fragile countries were as likely to be recommended as proposals from other countries, and resulting grants performed equally well except for lower performance of HIV/AIDS grants. English-speaking countries obtained more funding for TB and malaria than other countries. In conclusion, the independent TRP acted in line with the guiding principles of the Global Fund to direct funding to countries most in need without ex ante country allocation. The Global Fund appears to have promoted learning on how to design and implement large-scale programs in fragile and non-fragile countries. Other pooled financing mechanisms may consider TRP operating principles to generate high-quality demand, to promote learning and to direct resources to countries most in need.